Student Motivation Survey on Physical Education, Learning Sports, and Health During the COVID-19 Pandemic at MTsN 7 Wonosalam Jombang - Yully Wahyu Sulistyo; Noni Anggraini Octavia (Universitas Majalengka, 2023)
Learning in the covid-19 pandemic is a learning that is carried out online or online with the media used, namely the internet, and the learning process is carried out through websites, email and WhatsApp, the implementation of the learning process is also carried out remotely. This study aims to see how much motivation MTs Negeri 7 Wonosalam students have during the Covid-19 pandemic. This research is a quantitative descriptive research with a survey method. The research instrument used to collect data is a questionnaire that is distributed to students of MTs Negeri 7 Wonosalam class VII, VIII, and IX. The results showed that students' motivation in learning physical education in sports and health during the Covid-19 pandemic at MTs Negeri 7 Wonosalam in 2021 was moderate. This can be seen from the average results of the categories on 7 (seven) indicators, namely self-desire 53%, self-satisfaction 42%, good habits 46%, rewards 39%, punishment 52%, imitation of something 54%, and spirit 51%.Conclusion and Implications: Looking at the results of data analysis indicates that student learning motivation during the Covid-19 pandemic is in the moderate category, and for 1 indicators in the low category, namely the prize indicator. Further research is expected to add interview methods and add indicators such as initiative, commitment and other indicators, in addition to the indicators contained in this study.